Ulitilization of Refined Carrageenan as Cryoprotectant on Nila Frozen Surimi - . Uju; Finda Maryana; Joko Santoso (Jurnal Pengolahan Hasil Perikanan Indonesia, 2007)
During storage frozen, surimi will be lost part of functional protein characteristics, because of protein denaturation. For reducing this problem, some kinds of cryoprotectants were added during surimi processing. However, some cryoprotectants such as sucrose and sorbitol made taste of original surimi changing because of its sweetness. The aim of this research is to use refined carrageenan as cryoprotectant in surimi. The characteristic of refined carrageenan was used in this research include following sulfate content at 15.16, whiteness at 38.89%, viscosity at 180.5 cPS and gel strength at 490 g/cm2. During frozen storage for 8 weeks, the protein total and salt soluble decreased until 17-30% and 49-72% respectively. These decreasing caused the water holding capacity and gel strength reduced until 22-65% and 38-46 g/cm2 respectively. The using of refined carrageenan in surimi can reduce the rate of protein declining and can improve water holding capacity and gel strength. Using of refined carrageenan at 2% is the best concentration in this research.Key words: cryoprotectant, refined carrageenan, gel strength